Two methods of inclusion of biopsies of neoplasms in epoxy resin for teaching veterinary pathology - Ortloff Trautmann, Alexander (2020)
The current trend in the teaching of veterinary pathology is to promote the participation of students in their learning process and more autonomous work in practical activities. The traditional practice of neoplasm analysis involves macroscopic analysis of formalin-fixed biopsies and histopathological analysis. The objective of this study was to evaluate two tissue inclusion techniques with EPO-100 epoxy resin, material of low cost and easily accessible. The biopsies were obtained from tumours of dogs and cats in veterinary clinics in Temuco, Chile. Samples were processed with or without dehydration in ethanol and acetone before inclusion. The non-dehydrated samples retained all the details of the original sample, without altering the size, shape or colour, being more valued by students in practical activities than the dehydrated samples. The latter become transparent and lose the contrasts between their tissue components; however, they have the advantage of showing vascularization of the neoplasms. Both techniques complement each other and are a contribution to practical activities from the point of view of teaching and reduce the exposure of students to formalin.